Analisis Komperatif Pengukuran Kinerja Perusahaan dengan Metode Economic Value Added (EVA) dan Metode Tradisional - Lailatus Sa’adah; Muhammad Khariri Firdaus (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The purpose of this study is to find out how the financial performance of cigarette companies listed on the Indonesia Stock Exchange for the 2018-2022 period if measured by the Economic Value Added (EVA) method and the Traditional method, as well as to find out the comparison between the two. The research uses descriptive methods with a quantitative approach, in data collection with documentation studies. The data used as the basis for research are financial statements and annual reports. Furthermore, the data is processed using EVA analysis and ROA analysis. The results show that EVA's financial performance is good, with a positive EVA value. This means that the Company is able to create economic added value for investors and their business, while the ROA results are classified as not good, because they have a value below the industry standard of 30%, but all of them are positive values. This means that the Company is still able to make a profit from managing its assets. Based on the results of the comparison of EVA and ROA methods, it is known that the differences between all EVA companies have positive values. This means that the company has succeeded in creating economic added value for investors and their businesses. While the company's overall ROA value has a value below the industry standard of 30%. Thus, the performance in that year was classified as not good.